2018
DOI: 10.1051/cocv/2017004
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative anisotropic isoperimetric and Brunn−Minkowski inequalities for convex sets with improved defect estimates

Abstract: In this paper we revisit the anisotropic isoperimetric and the Brunn-Minkowski inequalities for convex sets. The best known constant C(n) = Cn 7 depending on the space dimension n in both inequalities is due to Segal [35]. We improve that constant to Cn 6 for convex sets and to Cn 5 for centrally symmetric convex sets. We also conjecture, that the best constant in both inequalities must be of the form Cn 2 , i.e., quadratic in n. The tools are the Brenier's mapping from the theory of mass transportation combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…The current best known bound for γ * (n) is cn −5 (log n) −10 , which follows by combining the general estimate of Kolesnikov-Milman [169], Theorem 12.2, with the polylogarithmic bound of Klartag, Lehec [164] on the Cheeger constant of a convex body in isotropic position improving on Yuansi Chen's work [76] on the Kannan-Lovász-Simonovits conjecture. Harutyunyan [137] conjectured that γ * (n) = cn −2 is the optimal order of the constant, and showed that it can't be of smaller order. Actually, Segal [232] observed that Dar's conjecture in [88] would imply that we may choose γ * (n) = cn −2 for some absolute constant c > 0.…”
Section: Classical Brunn-minkowski Theorymentioning
confidence: 99%
“…The current best known bound for γ * (n) is cn −5 (log n) −10 , which follows by combining the general estimate of Kolesnikov-Milman [169], Theorem 12.2, with the polylogarithmic bound of Klartag, Lehec [164] on the Cheeger constant of a convex body in isotropic position improving on Yuansi Chen's work [76] on the Kannan-Lovász-Simonovits conjecture. Harutyunyan [137] conjectured that γ * (n) = cn −2 is the optimal order of the constant, and showed that it can't be of smaller order. Actually, Segal [232] observed that Dar's conjecture in [88] would imply that we may choose γ * (n) = cn −2 for some absolute constant c > 0.…”
Section: Classical Brunn-minkowski Theorymentioning
confidence: 99%
“…The current best known bound for γ * (n) is cn −5 (log n) −10 , which follows by combining the general estimate of Kolesnikov-Milman [158], Theorem 12.2, with the polylogarithmic bound of Klartag, Lehec [153] on the Cheeger constant of a convex body in isotropic position improving on Yuansi Chen's work [73] on the Kannan-Lovász-Simonovits conjecture. Harutyunyan [128] conjectured that γ * (n) = cn −2 is the optimal order of the constant, and showed that it can't be of smaller order. Actually, Segal [215] observed that Dar's conjecture in [82] would imply that we may choose γ * (n) = cn −2 for some absolute constant c > 0.…”
Section: Classical Brunn-minkowski Theorymentioning
confidence: 99%